Penyuluhan Hukum Tentang Perlindungan Konsumen Di Era Digital Di Kalangan Masyarakat Kelurahan Bakunase Dua - Agustin Leni Magdalen Rohi Riwu; Samuel Haning; Marselinda Hege; Marthen Dillak (LPPI UMN AL WASHLIYAH, 2025)
This study aims to provide legal counseling on consumer protection in the digital era for the people of Bakunase Dua Village. Given the rapid development of technology and the many digital transactions that occur, many consumers do not yet understand their rights and the risks involved in these transactions. This community service activity involves legal counseling targeting digital transaction actors in the local community. Data collection was carried out through questionnaires given before and after the counseling activity, to measure changes in participants' understanding of consumer rights and how to protect themselves in digital transactions. The results of the community service showed that there was a significant increase in participants' understanding of their rights as consumers, as well as the procedures that can be taken to protect themselves from the risk of fraud and digital losses. Before the counseling, only a small number of participants understood digital consumer protection, but after the counseling activity, almost 90% of participants stated that they had a better understanding of how to protect themselves in the digital world. Thus, the purpose of this community service was achieved well, providing a positive impact on public legal awareness of consumer protection in the digital era. As a recommendation, similar activities need to be further developed by introducing practical training and digital media to reach more people, considering the increasingly rapid development of technology.